The Sharp Upper Bounds of the Hankel Determinant on Logarithmic Coefficients for Certain Analytic Functions Connected with Eight-Shaped Domains - Pongsakorn Sunthrayuth; Naveed Iqbal; Muhammad Naeem; Yousef Jawarneh; Sallieu K. Samura (Journal of Function Spaces)
The present study’s intention is to produce exact estimations of some problems involving logarithmic coefficients for functions belonging to the considered subcollection BTsin of the bounded turning class. Furthermore, for the class BTsin, we look into the accurate bounds of the Zalcman inequality, Fekete-Szegö inequality along with D2,1Gg/2 and D2,2Gg/2. Importantly, all of these bounds are shown to be sharp.